Students Error Analysis In Exponential And Logarithmic Equations - Tri Astuti Arigiyati; Welly Yumarsa; Eka Wahyuni Novianti; Betty Kusumaningrum (Hipotenusa : Journal of Mathematical Society, 2021)
Mathematics is one of the basic concepts needed by students at every level of education. However, students often have difficulty in understanding mathematics. This can be seen from the mistakes made when working on math problems. Errors made by students must be addressed immediately so that no more errors occur, especially on questions that have the same characteristics. The purpose of this study was to determine the percentage of conceptual errors, arithmetical errors, writing errors and the most common mistakes made by students on the subject of exponential and logarithmic equations. Sampling was done by using purposive random sampling technique. The data in this qualitative descriptive study were collected using test, interview, and documentation techniques. The instrument used to collect data was in the form of test questions and interview guide sheets. The data were analyzed by categorizing the types of errors into conceptual errors, arithmetic errors, and writing errors and then calculating the percentage of errors in each category. The results showed that the errors made by students in each category were conceptual errors of 53%, arithmetical errors of 34.78% and writing errors of 28.99%. The error that many students make is a conceptual error as much as 53% with a moderate error percentage category.